Medical English anxiety patterns among medical students in Sichuan, China - Deng, Jiaqi; Zhou, Kaiji; Al-Shaibani, Ghayth K. S. (Frontiers in Psychology, 2022)
This study adapts a Medical English Language Anxiety Scale (MELAS) based on Horwitz’s Foreign Language Classroom Anxiety Scale (FLCAS) and examines students’ anxiety in medical English vocabulary, listening and speaking, communication, literature reading, and academic paper writing. The biographical factors related to medical English language anxiety (MELA) were also tested. The questionnaire sets including five dimensions were distributed to the students from a medical university in Sichuan, China, and were statistically analyzed by using SPSS 22.0 and AMOS 21.0. By employing the adapted MELAS, it was found that 85.2% of the medical students surveyed suffered moderate and higher anxiety. Among all dimensions, students with listening and speaking anxiety recorded the highest (89.3%), followed by literature reading anxiety (86.6%), English academic writing anxiety (85.9%), communication anxiety (81.9%), and vocabulary learning anxiety (81.2%). We also found that the anxiety of rural medical students in each dimension was higher than that of urban medical students. This study suggests that English teachers should be fully aware of their students’ language anxiety situation, design interesting class activities, and create a relaxed English learning atmosphere in classroom teaching to make students less nervous when learning medical English in class.